Tofacitinib May Inhibit Myofibroblast Differentiation from Rheumatoid-Fibroblast-like Synoviocytes Induced by TGF-β and IL-6 - Piero Ruscitti; Vasiliki Liakouli; Noemi Panzera; Adriano Angelucci; Onorina Berardicurti; Elena Di Nino; Luca Navarini; Marta Vomero; Francesco Ursini; Daniele Mauro; Vincenza Dolo; Francesco Ciccia; et al. (MDPI AG, 2022)
During rheumatoid arthritis (RA), the pathogenic role of resident cells within the synovial membrane is suggested, especially for a population frequently referred to as fibroblast-like synoviocytes (FLSs). In this study, we assess the markers of myofibroblast differentiation of RA-FLSs by ex vivo observations and in vitro evaluations following the stimulation with both TGF-β and IL-6. Furthermore, we investigated the possible inhibiting role of tofacitinib, a JAK inhibitor, in this context. Myofibroblast differentiation markers were evaluated on RA synovial tissues by immune-fluorescence or immune-histochemistry. RA-FLSs, stimulated with transforming growth factor (TGF-β) and interleukin-6 (IL-6) with/without tofacitinib, were assessed for myofibroblast differentiation markers expression by qRT-PCR and Western blot. The same markers were evaluated following JAK-1 silencing by siRNA assay. The presence of myofibroblast differentiation markers in RA synovial tissue was significantly higher than healthy controls. Ex vivo, α-SMA was increased, whereas E-Cadherin decreased. In vitro, TGF-β and IL-6 stimulation of RA-FLSs promoted a significant increased mRNA expression of collagen I and α-SMA, whereas E-Cadherin mRNA expression was decreased. In the same conditions, the stimulation with tofacitinib significantly reduced the mRNA expression of collagen I and α-SMA, even if the Western blot did not confirm this finding. JAK-1 gene silencing did not fully prevent the effects of stimulation with TGF-β and IL-6 on these features. TGF-β and IL-6 stimulation may play a role in mediating myofibroblast differentiation from RA-FLSs, promoting collagen I and α-SMA while decreasing E-Cadherin. Following the same stimulation, tofacitinib reduced the increases of both collagen I and α-SMA on RA-FLSs, although further studies are needed to fully evaluate this issue and confirm our results.